High prevalence of anemia in Mexican women in poverty, Ensanut 100k - Fabiola Mejía-Rodríguez; Verónica Mundo-Rosas; Sonia Rodríguez-Ramírez; Mauricio Hernández-F; Armando García-Guerra; Eduardo Rangel-Baltazar; Luz María Gómez-Acosta; Teresa Shamah-Levy (Instituto Nacional de Salud Pública, 2019)
Objective. To estimate the prevalence and distribution of anemia in Mexican women and their association with sociodemographic factors and diet diversity. Materials and methods. We analyzed information of women in childbearing age. The Ensanut 100k is a probabilistic survey that overrepresents households with less economic capacity. Anemia was estimated using hemoglobin concentration. We collected sociodemographic and health information, food insecurity, and dietary diversity. Results. 34.3% of the women presented anemia, belong to tertile 3 of welfare status is a protective factor for anemia (OR= 0.26, 95%CI 0.16-0.61), and living in a household with food security, as well as high diversity of the diet in rural women (OR= 0.57, 95%CI 0.36-0.92). Conclusions. It is necessary to implement actions of detection and early attention of the anemia in women in childbearing age, identification of its underlying causes, strengthening and reformulation of strategies to prevent it.